Awareness of young people from different countries about risk factors influences on cardiovascular diseases - Cyboran, Katarzyna Aleksandra; Kuc, Monika; Kalicka, Maria; Korzec, Tomasz; Kania, Konrad (Journal of Education, Health and Sport, 2021)
One of the main reasons of deaths in the entire world is cardiovascular disease (CVD). Because of this, 17.9 million people died in 2019, which is 32% of deaths worldwide. Among these deaths, 85% were due to heart attack and stroke. More than 75% of deaths occur in low- and middle-income countries. Among the 17 million people under the age of 70 who died prematurely in 2019 due to non-contagious diseases, as many as 38% were caused by CVD. The most important risk factors for CVD include smoking, an unhealthy diet, obesity, inactivity, and alcohol consumption. These factors reflect the ongoing economic, social, and cultural changes. The development of this disease is also influenced by stress and genetic factors. Thanks to early diagnosis, it is possible to initiate treatment early and increase the patient's chance of survival. [1]